Effects of Sewage Discharge on Trophic State and Water Quality in a Coastal Ecosystem of the Gulf of California. (24th February 2014) - Vargas-González, Héctor Hugo; Arreola-Lizárraga, José Alfredo; Mendoza-Salgado, Renato Arturo; Méndez-Rodríguez, Lía Celina; Lechuga-Deveze, Carlos Hernando; Padilla-Arredondo, Gustavo; Cordoba-Matson, Miguel
Abstract : This paper provides evidence of the effects of urban wastewater discharges on the trophic state and environmental quality of a coastal water body in a semiarid subtropical region in the Gulf of California. The concentrations of dissolved inorganic nutrients and organic matter from urban wastewater primary treatment were estimated. La Salada Cove was the receiving water body and parameters measured during an annual cycle were temperature, salinity, dissolved oxygen, nitrite, nitrate, ammonia, orthophosphate, and chlorophyll a . The effects of sewage inputs were determined by using Trophic State Index (TRIX) and the Arid Zone Coastal Water Quality Index (AZCI). It was observed that urban wastewater of the city of Guaymas provided 1, 237 ton N yr − 1 and 811 ton P yr − 1 and TRIX indicated that the receiving water body showed symptoms of eutrophication from an oligotrophic state to a mesotrophic state; AZCI also indicated that the environmental quality of the water body was poor. The effects of urban wastewater supply with insufficient treatment resulted in symptoms of eutrophication and loss of ecological functions and services of the coastal ecosystem in La Salada Cove.